PERKAWINAN ANAK USIA DINI PERSPEKTIF HUKUM HINDU - Yase, I Kadek Kartika (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2021)
Marriage is a period that will go throgh each individual human being. It is stated in Hinduism that the purpose of marriage is not only to bear children and to fulfill biological needs, but also as a yadnya. Marriage for children must also be considered, both in terms of age and mentally. Age as a benchmark to determine a person's maturity, both in mind, mentality and emotion. In the Hindu concept, marriage should be carried out after finishing studying or the Brahmacari period. Providing opportunities for children to study and complete the brahmacari period, as well as an effort for parents to prevent early marriage. In addition, taking a good approach or communication relationship with children and controlling children's relationships and providing religious doctrine are also important things in preventing early childhood marriage. On the other hand, the government has made a minimum age restriction for marriage, as well as an effort to suppress the occurrence of early childhood marriages. The socialization of the negative impact of early childhood marriage is also intensively carried out through related parties. However, the spearhead of preventing early childhood marriage are parents or family. For parents who interact more and directly with children and can also give permission and whether or not they want to marry.